Preservation of Bilateral Nasoseptal Flap Vascular Pedicles: Rescue Flap Modification for Endonasal Skull Base Surgery. (23rd August 2013) - Griffiths, Chester F.; Cutler, Aaron; Duong, Huy; Karimi, Kian; Barkhoudarian, Garni; Carrau, Ricardo; Kelly, Daniel
Abstract : Objectives: The nasoseptal flap (NSF) has significantly reduced the incidence of postoperative cerebrospinal fluid (CSF) leaks in endoscopic skull base surgery. In the traditional endonasal approach, the NSF vascular pedicle is frequently sacrificed during the sphenoidotomy, thus eliminating the flap as a reconstruction option should a large CSF leak be encountered. In addition, extensive mucosal removal may result in postoperative crusting, hyposmia, or anosmia. Methods: Introduce the concept and surgical technique of bilateral mucosal and septal olfactory strip (SOS)‐preserving rescue flaps, ensuring availability of both vascular pedicles while also promoting rapid healing and reducing the risk of postoperative epistaxis and olfactory dysfunction. Retrospective analysis of patient records who underwent endoscopic tumor/cyst removal with bilateral nasoseptal rescue flaps from August 2011 until December 2012 (15 months). Results: In total, 95 (80%) of 118 patients (mean age 51 years; 78 pituitary adenomas, 7 RCC, 10 other pathologies), including 20 (21%) with prior surgery, underwent bilateral rescue flaps. Unencumbered visualization, mobility of the endoscope and instruments, and access to the sphenoid sinus/parasellar region was experienced in all cases. One patient underwent conversion to a formal NSF without complication. No patient had postoperative arterial epistaxis. Conclusions: This modification of the nasoseptal rescue flap technique is an effective bilateral mucosal preserving approach. In addition to maintaining both vascular pedicles, it likely reduces the risk of major postoperative epistaxis, preserves olfaction by maintaining the SOS, and promotes rapid mucosal healing while not hindering exposure or limiting instrument maneuverability.